2021
DOI: 10.3390/microorganisms9122441
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bacterial Strains Isolated from Coastal Water for Wastewater Treatment and as Aqua-Feed Additives

Abstract: Bacteria have various and sustained effects on humans in various fields: molecular biology, biomedical science, environmental/food industry, etc. This study was conducted to evaluate the wastewater treatment capacity and feed-additive fish-growth effect of four strains of bacteria: Pseudoalteromonas mariniglutinosa, Psychrobacter celer, Bacillus albus, and Bacillus safensis. In a wastewater degradation experiment, (i) nitrate-N and nitrite-N were removed within 1 h in all of the 4 bacterial strains; (ii) the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
(100 reference statements)
0
2
0
1
Order By: Relevance
“…Bakteri ini mampu memanfaatkan amonium dan nitrat sebagai sumber nitrogen serta dapat menurunkan kadaramonia dalam perairan. Cara penguraian limbah, yaitu dengan cara oksidasi yaitu pemecahan senyawa kompleks menjadi sederhana (Kim et al, 2021) Pada sebuah tambak udang, limbah organik yang dihasilkan dapat berasal dari sisa pakan maupun feses hewan ternak. Limbah organik dapat meningkatkan kadar amonia yang toksik bagi biota air dengan batas tertinggi 0,1 mg/l.…”
Section: Bakteri Pendegradasi Logam Beratunclassified
“…Bakteri ini mampu memanfaatkan amonium dan nitrat sebagai sumber nitrogen serta dapat menurunkan kadaramonia dalam perairan. Cara penguraian limbah, yaitu dengan cara oksidasi yaitu pemecahan senyawa kompleks menjadi sederhana (Kim et al, 2021) Pada sebuah tambak udang, limbah organik yang dihasilkan dapat berasal dari sisa pakan maupun feses hewan ternak. Limbah organik dapat meningkatkan kadar amonia yang toksik bagi biota air dengan batas tertinggi 0,1 mg/l.…”
Section: Bakteri Pendegradasi Logam Beratunclassified
“…Traditional physicochemical methods (such as separation, landfill, flocculation, electrolysis, etc.) [ 3 , 4 ] for the treatment of waste oil are expensive and create secondary pollution problems [ 5 ]. One study showed that the degradation rate of hot pot waste oil by Klebsiella pneumoniae LZU10 was 37.7% in 48 h [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…29,30 It is one of the most efficient bacteria in treatment of wastewater. 31,32 B. subtilis is an aerobic decomposer which is known to degrade heavy metals and reduce toxicity of water. 33,34 In this article we shall witness the effect of B. subtilis on wastewater which was taken as a sample from an industry.…”
Section: Introductionmentioning
confidence: 99%